2017
DOI: 10.1111/obr.12550
|View full text |Cite
|
Sign up to set email alerts
|

The effect of flaxseed supplementation on body weight and body composition: a systematic review and meta‐analysis of 45 randomized placebo‐controlled trials

Abstract: Summary Flaxseed consumption may be inversely associated with obesity; however, findings of available randomized controlled trials (RCTs) are conflicting. The present study aimed to systematically review and analyse RCTs assessing the effects of flaxseed consumption on body weight and body composition. PubMed, Medline via Ovid, SCOPUS, EMBASE and ISI Web of Sciences databases were searched up to November 2016. Mean changes in body composition indices including body weight, body mass index (BMI) and waist circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 85 publications
(486 reference statements)
3
40
2
2
Order By: Relevance
“…However, flaxseed oil consumers showed more substantial weight reduction which was statistically different from sunflower group, indicating that flaxseed oil exerted an additional effect on weight and BMI. Accordingly, a meta-analysis suggested that consumption of flax seeds, flaxseed oil or flaxseed lignan results in significant decrease of weight, BMI and waist circumference (43) . Clinical trials have shown that flaxseed fibre may induce higher postprandial satiety and fullness without affecting ghrelin, cholecystokinin, glucagon like peptide-1 and energy intake (44) .…”
Section: Adipositymentioning
confidence: 99%
“…However, flaxseed oil consumers showed more substantial weight reduction which was statistically different from sunflower group, indicating that flaxseed oil exerted an additional effect on weight and BMI. Accordingly, a meta-analysis suggested that consumption of flax seeds, flaxseed oil or flaxseed lignan results in significant decrease of weight, BMI and waist circumference (43) . Clinical trials have shown that flaxseed fibre may induce higher postprandial satiety and fullness without affecting ghrelin, cholecystokinin, glucagon like peptide-1 and energy intake (44) .…”
Section: Adipositymentioning
confidence: 99%
“…Previous studies have supported the beneficial effects of nutraceuticals and functional foods such as green tea, cranberry, and flaxseed in the management of obesity and subsequent associated complications (Baboota et al, 2013;Hirai et al, 2010;Kovacs & Mela, 2006;Kowalska & Olejnik, 2016;Mohammadi-Sartang et al, 2017;Phung et al, 2010). Pomegranate (Punica granatum) is known as another functional food with beneficial health effects including hypotensive, hypocholesterolaemic, and antiatherosclerotic effects (Viuda-Martos, Fernández-López, & Pérez-Álvarez, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach to control the NAFLD parameter is dietary adjuncts such as medicinal plants that encompass various pharmacological properties and probably fewer adverse effects compared with chemical drugs (Benzie & Wachtel-Galor, 2011). Previous investigations have demonstrated the therapeutic effects of functional foods and medicinal plants such as green tea, cranberry, and flaxseed in the management of NAFLD and its subsequent complications (Accattato et al, 2017;Hirai et al, 2010;Kovacs & Mela, 2006;Kowalska & Olejnik, 2016;Mohammadi-Sartang et al, 2017;Phung et al, 2010).…”
mentioning
confidence: 99%